2002
DOI: 10.1097/01.asn.0000027871.86296.92
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Renal Function in Elderly Patients with Isolated Systolic Hypertension

Abstract: Abstract. Several reports suggest that markers of renal function such as serum creatinine, serum uric acid, and urinary excretion of protein may be related to cardiovascular complications and mortality. This study analyzed the data from the Syst-Eur trial, which was a randomized, placebo-controlled, double-blind intervention trial in elderly patients with isolated systolic hypertension. The purpose was to evaluate whether serum levels of creatinine and uric acid and urinary protein excretion at entry are relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
119
0
8

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(131 citation statements)
references
References 28 publications
(30 reference statements)
4
119
0
8
Order By: Relevance
“…1 Proteinuria is one of the clinical parameters for diagnosing renal damage, particularly in glomerular hypertension, and it has been reported to be a risk factor and predictor of cardiovascular events. 2,3 Therefore, suppression of proteinuria is a major goal in the treatment of hypertensive patients with CKD. The renoprotective effects of angiotensin receptor blockers (ARBs) and angiotensin-converting enzyme inhibitors (ACEIs) have been shown earlier.…”
Section: Introductionmentioning
confidence: 99%
“…1 Proteinuria is one of the clinical parameters for diagnosing renal damage, particularly in glomerular hypertension, and it has been reported to be a risk factor and predictor of cardiovascular events. 2,3 Therefore, suppression of proteinuria is a major goal in the treatment of hypertensive patients with CKD. The renoprotective effects of angiotensin receptor blockers (ARBs) and angiotensin-converting enzyme inhibitors (ACEIs) have been shown earlier.…”
Section: Introductionmentioning
confidence: 99%
“…Proteinuria is one of the clinical parameters for diagnosing renal damage, especially glomerular hypertension, and is a risk factor and predictor for cardiovascular events (3). Reducing glomerular pressure is a principal strategy for reducing proteinuria in hypertensive patients (4).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Schillaci et al 28 found that creatinine concentrations, even in the conventionally accepted reference range, behaved as a predictor of cardiovascular morbidity in hypertensive patients without renal artery stenosis. Likewise, De Leeuw et al 29 showed in the Systolic Hypertension in Europe study (Syst-Eur) that higher levels of serum creatinine are associated with an increased number of cardiovascular events and a higher mortality in patients with isolated systolic hypertension. Thus, one may conclude that serum creatinine concentrations reflect the presence of subclinical atherosclerosis.…”
Section: Discussionmentioning
confidence: 97%